Captive spawning and larval rearing of California yellowtail (Seriola lalandi). Issue 5 (19th January 2012) - Stuart, Kevin R.; Drawbridge, Mark A.
Abstract A captive population of California yellowtail (Seriola lalandi) was used to document spawning patterns, including measures of egg production, population fecundity and egg and larval quality from 2007 to 2010. Spawned eggs were also used to document larval development and to develop rearing techniques for aquaculture in the region. Broodstock growth and condition factor were best when feeding rations were maintained at 10–15% body weight week−1 during the warm summer months. A winter ration based on satiation feeding was typically 4% body weight week−1. During the 4‐year study period, the only broodstock health issue was an infestation by the parasitic gill fluke Zeuxapta seriolae, which was readily treated. Spawning occurred naturally in the 140 m3 tank when the ambient water temperature reached 16°C and ended when the temperature exceeded 22°C. Egg production reached a maximum in 2010 when 43 spawn events were recorded from a pool of nine females yielding 36.8 million eggs in total. The average female size at this time was 20 kg, which equated to a total annual population fecundity of approximately 226 000 eggs kg−1 female year−1. Larval rearing trials yielded survival rates as high as 5.8% from egg to 50 days post‐hatch (dph). Successful larval culture methods included the addition of algae paste for green water culture, rotifers (20 rotifers mL−1) at 2 dph and Artemia (5 Artemia mL−1) at 6 dph. Larvae were transferred from the incubation tank at 10 dph to a shallower tank with 33% greater surface area to accommodate the larvae's strong orientation to surface waters. This research represents the first documentation of successful spawning and larval rearing for S. lalandi in the eastern Pacific.